Dacryocystitis due to Sporothrix brasiliensis: a case report of a successful clinical and serological outcome with low‐dose potassium iodide treatment and oculoplastic surgery. (1st April 2015) - Marques de Macedo, P.; Sztajnbok, D.C.N.; Camargo, Z.P.; Rodrigues, A.M.; Lopes‐Bezerra, L.M.; Bernardes‐Engemann, A.R.; Orofino‐Costa, R.
Summary: Sporothrix brasiliensis is the main species of the S. schenckii complex implicated in the zoonotic epidemics of sporotrichosis in Rio de Janeiro, Brazil. Epidemiological features have been already described, such as zoonotic transmission by cats and increased frequency of atypical clinical aspects. The involvement of the face by contact with cats is common in childhood; as a result, ophthalmic manifestations have increased. We report a case of acute dacryocystitis in a 9‐year‐old girl. A calmodulin‐based molecular phylogeny was used to identify the agent as S. brasiliensis . This is a rare type of presentation, usually complicated with nasolacrimal duct occlusion. The patient was cured without sequelae after treatment with a low dose of saturated solution of potassium iodide and decompressive oculoplastic surgery. Therapeutic options and considerations of aetiological agents and serology are discussed.